2022
DOI: 10.1097/md.0000000000031813
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between novel Coronavirus pneumonia and Parkinson’s disease

Abstract: The hypothesis is that there is 0a relationship between Parkinson's disease and coronavirus disease 2019 . By summarizing the pathogenesis of Parkinson's disease and COVID-19 and the impact of COVID-19 on the central nervous system, the relationship between Parkinson's disease and COVID-19 was analyzed, including whether Parkinson's disease is a predisposition factor for COVID-19 and whether COVID-19 causes the occurrence of Parkinson's disease. Discuss the impact of COVID-19 on patients with Parkinson's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Parkinson’s disease (PD) ranks second among all neurodegenerative disorders in terms of its morbidity, and its prevalence is rising ( 1 , 2 ). It has been reported that PD affects more than 6 million people worldwide, and that number may rise to 10 million by 2030 ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) ranks second among all neurodegenerative disorders in terms of its morbidity, and its prevalence is rising ( 1 , 2 ). It has been reported that PD affects more than 6 million people worldwide, and that number may rise to 10 million by 2030 ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 Myopia, however, has been little researched in this context, despite the known retinal structural consequences, 26 as well as the known importance of retinal image quality and function on normal ocular development. 27,28 Nonetheless, speculation may be growing in this area; recently, a review paper was published examining the Chinese and Western medicinal perspectives on the relationship between the gut microbiota and the pathological mechanisms of myopia in adolescents, 29 and one paper has characterised the ocular microbiome between low and high myopia, finding a higher relative abundance of Proteobacteria at the phylum level and Acinetobacter at the genus level in patients with high myopia. 30 In addition, studies on the gut microbiome of myopic individuals are limited.…”
mentioning
confidence: 99%
“…A review by Xi et al 29 proposes a possible mechanism linking myopia to the gut microbiome that involves changes in dopamine production. Certain gut bacteria, such as enterococci, may possess homologues of enzyme genes similar to those found in mammals for the production of dopamine 29,32,33 via the existing phenylalanine-tyrosinedopa-dopamine pathway.…”
mentioning
confidence: 99%
See 2 more Smart Citations